Hubungan Antara Penggunaan Gadget dengan Perkembangan Bahasa Anak Usia Dini - Arum Kusuma Dewi; Yuyun Yulianingsih; Tuti Hayati (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2019)
The results of the preliminary study in RA Al-Wafi's group showed that, there were several problems related to the use of gadgets with language development including many parents who relied on gadgets to make their children become